Al-Fārābī’s Political Strategy in his Account of Prophecy - Al-Tawallba, Mohammad Abdullah; Ali, Duaa khalil; Al-Khalayleh, Ayman; Alsharab, Asma (Jordan Journal of Social Sciences, 2024)
This study aimed to explore the possibility that the theory of prophecy within Al-Fārābī’s philosophy can be explained as an expression of an ideology which sought to provide solutions to some problems that the Islamic state was experiencing during his time. This ideology was depicted in the form of elevating the philosopher over the prophet. Al-Fārābī's theory of prophecy was first introduced with focus on how he distinguished between the philosopher and the prophet, highlighting the differences between the rational and imaginary faculties and how he employed these differences to serve the Islamic community. Al-Fārābī’s strategy of defending prophecy can be conceived as a sort of maneuvering to monopolize power for the Prophet and his descendants, i.e., even in favor of the Twelve Imams (al-A’immah al-Ithnā ‘ashar), who were considered free of errors. According to Al-Fārābī, a philosopher never existed in Islam. Given the historical situation, the defense of the Prophet was necessary until an Islamic philosopher existed.